Hip Arthroscopy After Total Hip Arthroplasty Is Rare (0.04%) and May be Contralateral - Caitlin A. Orner, M.D.; Michael B. Banffy, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation)
Purpose: To determine the patient demographics and incidence of hip arthroscopy after total hip arthroplasty using the PearlDiver database. Methods: This is a retrospective study of patients undergoing total hip arthroplasty and arthroscopic hip surgery. The PearlDiver Claims Database was queried using Current Procedural Terminology (CPT) codes for records from 2010 to 2021. Inclusion criteria were presence of a hip arthroplasty CPT code, followed by a hip arthroscopy CPT code. Additional data collected included age, sex, and time between surgeries. A subanalysis for International Classification of Diseases (ICD), Ninth (-9) and Tenth (-10) Revision, codes was completed to estimate association with iliopsoas tendinitis. Results: Query of the database showed that 314 patients had a hip arthroscopy code after a hip arthroplasty code. In total, 0.04% of patients who underwent arthroplasty subsequently underwent arthroscopy; 63.4% were female. Mean age was 58.2 ± 12.2 years at time of arthroscopy. A total of 214 (72.3%) patients had a CPT code for synovectomy, 56 (18.9%) for loose body removal, and 44 (15.3%) for diagnostic arthroscopy. The mean time from arthroplasty code to arthroscopy code was 2.5 ± 2.0 years. In total, 105 patients (33.4%) also had an ICD-10 diagnosis code for iliopsoas tendinitis, and 116 (36.9.0%) had the ICD-9 code for enthesopathy of hip. Conclusions: In this study, we found that hip arthroscopy after hip arthroplasty is uncommon but occurs more frequently in female patients, is undertaken in a broad age range of patients, and often is associated with a diagnosis of iliopsoas or hip tendinitis. Level of Evidence: Level IV, retrospective case series.